PRINSIP PENGELOLAAN ZAKAT MENURUT AL-QUR’AN (KAJIAN PADA SURAT AL-TAUBAH [9]: 103, DENGAN METODE TAHLILI DAN PENDEKATAN FIQHY) - Muhammad Aziz (Al Hikmah: Jurnal Studi Keislaman, 2015)
The management of zakat in modern times, has made a significant development, especially Musim-majority countries. Of course, it requires a theological foundation, either from the Qur'an or Sunnah (Prophet tradistions). The fragility of theological foundation will lead to possible criticism from Muslims. This study will answer two questions, first; how is the interpretation of the principle of zakat management based on QS al-Taubah: 103? Second, how is the viewpoints ulema (Muslim scholars, especially engaged in Islamic jurisprudence/figh) in interpreting the verse?This study uses a qualitative approach by using a descriptive-comparative-analytical study, namely describing the ulema interpretations related to the Surah al-Taubah: 103, coparing the viewpoints of fiqh ulema and then analyzing it critically. The comparative study uses several scholarly arguments of fiqh ulema.This study concludes that basically zakat management is something that is very vital in the process of utilizing zakat as one of the economic pillars in the public distribution. The essential principle which must be addressed in the zakat management is the managerial aspect and professional, effective, skillful human resources that are capable of dealing with the entire forms of utilization of zakat, and this system can only be done by an agency or institution that is powerful and able to reach the whole area of the poor.